Investigating the effect of computer workstation setups on musculoskeletal symptoms, oxygen saturation, and perceived fatigue - Tiong, Jing Yin (2023)
Symptoms of musculoskeletal disorders are common among office workers worldwide. Several studies have documented self-reported data on musculoskeletal disorder symptoms among office workers, though there are limited published studies focusing on summarisation of assessment results by ergonomics practitioners. In addition, the relationship between the effect of upper limbs posture and office workstation set-ups to muscle oxygen saturation among office workers is unclear. The main objective of this study is to compare the percentage of muscle oxygen saturation and perceived fatigue ratings between four different experimental conditions among representative computer users. The prevalence rates of musculoskeletal disorder symptoms, ergonomics risk factor exposure patterns, and root causes of these exposures among office workers in Malaysia was investigated. The study also aimed to compile lists of common recommendations by ergonomists to control the exposures. The methodology was segregated into two phases to achieve each objective. Phase 1 includes a review of 399 ergonomics assessment reports which obtained from consulting ergonomic company. In phase 2, a repeated measure experiment was conducted among 15 subjects with four experimental conditions through the use of Moxy Muscle Oxygen Monitor device and perceived fatigue rating scale. The findings from phase 1 showed high MSD symptoms prevalence of varying degrees (87%) among sample population. Body parts that were mostly affected among sample population include shoulder (42%), lower back (38%) and neck (32%). Common ergonomics risk factors among office workers include poor postures (97%), static loading (90%), and contact stress (74%), in which the root causes of these risk factors can be traced back to substandard furniture designs as well as poor work habits. Most common recommendations by ergonomists were related to proper adjustments of chair and monitor, as well as improvement of sitting postures and technique of using mouse. Data analysis from phase 2 showed statistically significant trends (P ≤ 0.05) of muscle oxygen saturation level in different workstation setups. In addition, the findings revealed that the perceived fatigue ratings on shoulder, upper arm and lower arm are lowest (P ≤ 0.05) in workstation condition where subject can adopt neutral postures. In conclusion, this study provides insight on patterns and root causes of exposure to ergonomics risk factors among Malaysian office workers from ergonomists point of view. Besides, the findings also provide guidance for organization, management and office workers focus on improving their office workstation setups, especially for workers who are spending most of the working time on the computer.